2021
DOI: 10.1007/s10311-021-01222-x
|View full text |Cite
|
Sign up to set email alerts
|

High resolution mapping of nighttime light and air pollutants during the COVID-19 lockdown in Wuhan

Abstract: The novel coronavirus (COVID-19) has induced unprecedented improvements of air quality due to drastic shrinking of human activities during the pandemic lockdown in 2020. While declines of most air pollutants have been globally evidenced in most cities worldwide, there is few detailed spatial knowledge at local scale. Therefore, we present here a high resolution mapping of the 2018-2020 evolution of human activities and air pollutants in Wuhan. Human activities were assessed by nighttime light radiance. We meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…A study by Zheng et al ( 2021 ) comparing air pollution data in Wuhan from 2020 with previous years showed that particulate matter and nitrogen dioxide levels were strongly reduced, carbon monoxide levels were less reduced owing to ongoing power industries, sulfur dioxide levels first decreased and then increased to exceed the 2018–2019 values due to coal combustion, and, finally, ozone concentrations were even higher as a result of lower nitrogen oxide air pollution and the weekend effect. Similarly, Wang et al ( 2020 ) showed that during the lockdown, the average daily concentrations in urban areas decreased by 47.9% for coarse particulate matter, 42.7% for PM 2.5 , 58.4% for nitrogen dioxide, 28.6% for sulfur dioxide, and 22.3% for carbon monoxide as compared to the same period in 2019.…”
Section: Associations Between Chronic Ambient Air Pollution and Cardi...mentioning
confidence: 99%
“…A study by Zheng et al ( 2021 ) comparing air pollution data in Wuhan from 2020 with previous years showed that particulate matter and nitrogen dioxide levels were strongly reduced, carbon monoxide levels were less reduced owing to ongoing power industries, sulfur dioxide levels first decreased and then increased to exceed the 2018–2019 values due to coal combustion, and, finally, ozone concentrations were even higher as a result of lower nitrogen oxide air pollution and the weekend effect. Similarly, Wang et al ( 2020 ) showed that during the lockdown, the average daily concentrations in urban areas decreased by 47.9% for coarse particulate matter, 42.7% for PM 2.5 , 58.4% for nitrogen dioxide, 28.6% for sulfur dioxide, and 22.3% for carbon monoxide as compared to the same period in 2019.…”
Section: Associations Between Chronic Ambient Air Pollution and Cardi...mentioning
confidence: 99%
“…With the world still waiting for an effective mass vaccination using the developed anti-COVID-19 vaccines (Costanzo et al 2021 ; He et al 2021 ) and despite the efforts by pharmaceutical companies and the scientific community to develop effective therapies through drug repurposing (Borbone et al 2021 ; Costanzo et al 2020 ; Kumawat et al 2021 ; Khan et al 2021 ), herbal medicine (Vicidomini et al 2021b ) and other recently proposed approaches (Vicidomini et al 2021a ; Wang et al 2020b ), SARS-CoV-2 and its mutations remain a major global issue leaving our future unclear. COVID-19 has also had an environmental impact on the planet, and while initial data from ESA (European Space Agency) and NASA (U.S. National Aeronautics and Space Administration) seemed to suggest that pollution in the first epicenters of COVID-19 such as the Hubei region of China, Italy, Spain and the USA had reduced significantly (up to 30%) (Muhammad et al 2020 ), in the subsequent phases of the pandemic, an increasing pollution trend was recorded globally (Wang et al 2020a ; Zheng et al 2021 ; Shehzad et al 2021 ). Of equal importance, there has also been an increase in plastic pollution (Gorrasi et al 2020 ; Ufnalska and Lichtfouse 2021 ) due to face masks, gloves and other single-use COVID-19-related plastics that are posing a major risk for marine ecosystems and aquatic organisms (Aragaw 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tanvir et al ( 2021 ) revealed that vertical column densities (VCDs) of formaldehyde decreased 24% during the strictest lockdown period. Although significant reductions of primary pollutants were found, ozone over eastern and northern China significantly rebounded during the lockdown (Yuan et al 2021 ; Zhao et al 2021 ; Zheng et al 2021 ; Zhu et al 2021 ). As a result, the enhanced role of secondary formation in haze formation was revealed (Chang et al 2020 ; Huang et al 2021 ; Le et al 2020 ; Meng et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%